06.08 Low-dose il-2 therapy in refractory sle: results from a single centre phase i/iia clinical trial. (1st March 2017) - Humrich, Jens Y; Spee-Mayer, Caroline von; Siegert, Elise; Bertolo, Martina; Abdirama, Dimas; Rose, Angelika; Enghard, Philipp; Hiepe, Falk; Alexander, Tobias; Radbruch, Andreas; Burmester, Gerd-Rüdiger; Riemekasten, Gabriela
Abstract : Background/purpose: Interleukin-2 (IL-2) is crucial for the growth and survival of regulatory T cells (Treg), and thus for the control of autoimmunity. In previous studies we revealed the significance of an acquired IL-2 deficiency and related Treg defects in the pathogenesis of systemic lupus erythematosus (SLE) . 1, 2 Accordingly, we showed that low dose IL-2 therapy is capable to correct Treg defects in SLE patients. 2, 3 Here, we conducted a combined phase I/IIa single centre clinical trial addressing the safety, tolerability, immunological responses and clinical efficacy of a subcutaneous low-dose IL-2 therapy in patients with refractory and active SLE. Methods: 10 patients with active and refractory SLE (SLEDAI ≥6) were enrolled into the trial and 2 patients were treated "off-label" in advance with the same regimen. The therapeutic regimen consisted of four treatment cycles each with daily subcutaneous injections of recombinant human IL-2 (aldesleukin) at single doses of 0.75, 1.5 or 3.0 million IU on five consecutive days. Cells from peripheral blood were analysed by flow cytometry at every study visit before and one day after each treatment cycle. The primary objective was to show an increase in the percentage of CD25hi cells among CD3 + CD4 + Foxp3 + CD127lo Treg cells by at least 100% (2 fold) after the 4th treatment cycle compared to baseline. Safety and tolerability were evaluated descriptively. Secondary objectives included the clinical responses assessed by SLEDAI and changes in serological and other immunological parameters. Results: All 12 patients showed an effective and cycle-dependent increase in the percentage of CD25hi cells among Treg (p<0.001). 10 patients showed a reduction in SLEDAI (83.3%, p<0.05) and 8 patients achieved a clinical response (66.7%) with a complete disappearance of clinical manifestations such as rash, arthritis, myositis and alopecia. Levels of complement were significantly increased after the treatment compared to baseline (p<0.05). No reduction in levels of anti-dsDNA-Abs was observed. Treatment-related adverse events were generally mild and transient. Conclusion: Low-dose IL-2 therapy is capable to safely and selectively expand the Treg population and to decrease disease activity in patients with active and refractory SLE. This study provides the basis for larger and placebo-controlled clinical trials. References: 1. Humrich, et al . Homeostatic imbalance of regulatory and effector T cells due to IL-2 deprivation amplifies murine lupus. Proc Natl Acad Sci USA. 2010; 107(1):204–209. 2. von Spee-Mayer, et al . Low-dose interleukin-2 selectively corrects regulatory T cell defects in patients with systemic lupus erythematosus. Ann Rheum Dis. 2016 ;75(7):1407–15. 3. Humrich, et al . Rapid induction of clinical remission by low-dose interleukin-2 in a patient with refractory SLE. Ann Rheum Dis. 2015 ;74(4):791–2.